IMPLEMENTASI PROGRAM PENGURANGAN SAMPAH DI KOTA BATAM TAHUN 2018 - Solihin, Muhammad; Mulda, Rahmayandi (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan ilmu Politik Universitas Riau Kep, 2019)
Waste sorting is not so massive in Batam City. So indeed from the source of waste most of the waste has not been sorted. The problem of waste in the city of Batam will be complicated if it is not planned carefully, especially in this case is the reduction of waste. The specific purpose of this study was to determine the implementation of the waste reduction program in Batam City in 2018 and what factors influenced its success. Place of research in the office of Batam City Environment Agency for Waste Management and the location of waste reduction partners. This type of research uses a qualitative approach with descriptive analysis. Data collected for interview, observation and documentation research. The sample technique uses purposive sampling. The results of the study, First: There are no input indicators derived regulations in the management of household waste in the city of Batam and human resources and organization of waste bank management units are still very minimal. Second: The output indicator, the rubbish bin in the houses (the source of rubbish) still consists of one type of rubbish bin so that the rubbish is indeed not disaggregated from the house. The TPS3R and Waste Bank are considered not yet running optimally because the amount is very small so that the reduction of waste is also not significantly reduce waste. Factors that influence success are generally constrained by the lack of resources, especially for TPS3R managers and the Waste Bank does not have permanent incentives from the government.